PELAKSANAAN PENDAFTARAN AKTA PEMBERIAN HAK TANGGUNGAN YANG MELEBIHI BATAS WAKTU PENDAFTARAN BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN (Studi Kasus di Kantor Pertanahan Kabupaten Boyolali) - SUWANDI, SUWANDI (Dinamika Hukum, 2019)
The purpose of this study is to: 1) Review and analyse the implementation of the registration of a Deed Granting a dependent by a conveyancer exceeding the deadline for registration at the Land Office Boyolali Regency. 2) review and analyze the consequences of the ruling against Certificate Awarding a late Dependent was enrolled in Boyolali District Land Office. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interviews and observations. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) the implementation of the registration of a deed Granting a dependent by a conveyancer exceeding the deadline for registration at the Land Office Boyolali Regency implemented can still be accepted, but the Office Land tenure obligates a conveyancer Boyolali Regency too late to make the affidavits and statements late accompanied reasons of delay and file registration rights that dependents can receive and remain unprocessed because in section 114 subsection (7) Regulation of the Minister of State Agrarian/head of National Land Agency Number 3 Year 1997 regarding the implementation of the provisions of the Government Regulation Number 24 year 1997 Regarding land registry has mentioned that the "conditions of registration Rights Agreements should be implemented by the Office of Although the land delivery of files by a conveyancer is done after the set time. " 2) due to the ruling against Certificate Awarding a late Dependent was enrolled in the Office of land and Boyolali district, namely the recent Dependent Right of birth, but does not affect the validity of the registered Deed of Grant Agreements. The consequences will be over by the time limit register Deed of Grant Agreements by Land Deed Official, administrative sanctions against incurring conveyancer that is in the form of an oral reprimand if the first still do delay, if repeated then Land Office Boyolali Regency will give reprimand in writing to the conveyancer in order to pay attention to the conditions of the time limit that has been set. Late registration also gives rise to a loss against the parties concerned in particular the lender because the registration rights agreements be determinant the birth rights of dependents. Yet not cause the Deed of Grant Agreements tied up inclusion of third parties against the promises that are enforced by the lender and the owner of the rights to objects of dependents. Registration rights agreements aimed so that the certificate of entitlement Dependants can be born and creditors as stakeholders protected by law the rights of preferred creditors as Dependents who have positions take precedence in the payment of debt of the debtor. Keywords: Registration Certificate Granting Dependents, Exceeding the Time Limit